Advances in the UK Toward NDE 4.0. Issue 5 (1st November 2020) - Brierley, N.; Smith, R. A.; Turner, N.; Culver, R.; Maw, T.; Holloway, A.; Jones, O.; Wilcox, P. D.
ABSTRACT: In the UK, the NDE community is making a coordinated effort to underpin and enable the full benefits of the large-scale trend toward comprehensive digitalization and automation of industrial processes and assets, frequently referred to as "Industry 4.0". Certain facets of what is now considered to be NDE 4.0 have been the subject of research for some time and have already gained industrial traction, while others are quite new, with unexplored potential and pitfalls. However, in these areas there is scope for learning from progress in fields outside of, but related to, NDE such as dimensional metrology. This paper reviews progress to date based on UK activities, considers some planned and potential research tasks in this domain, and highlights the major challenges the NDE community must tackle. In particular, as interoperability and data reuse are key features of Industry 4.0 practices, international and cross-domain efforts on data format standardization are needed. It is clear that, without the NDE community stepping up to the challenge, much of Industry 4.0 cannot be realized; yet if the NDE 4.0 vision is implemented comprehensively, NDE has the potential to become more capable, more valuable, and therefore more highly valued.